Clonal B-cell lymphocytosis of marginal zone origin. Issue 1 (March 2017) - Xochelli, Aliki; Oscier, David; Stamatopoulos, Kostas
Abstract: Monoclonal B cell Lymphocytosis (MBL) is the term used to characterize individuals presenting with lymphocytosis in the absence of lymphadenopathy, organomegaly or any other features suggestive of an active disease. Based on the immunophenotypic findings, MBL cases are sub-categorized into chronic lymphocytic leukemia (CLL)-like, atypical CLL and non-CLL MBL. The latter corresponds to cases with immunophenotypic features suggestive of post germinal center derivation and still represents a diagnostic conundrum. Recent studies are starting to shed light on the true biological nature and clinical significance of this entity and have led to the introduction of the novel term clonal B lymphocytosis of marginal-zone origin (CBL-MZ); as well as the acknowledgement of CBL-MZ in the latest (2016) update of the WHO classification for lymphoid malignancies. Here we provide an overview of relevant research concerning non-CLL MBL and discuss clinico-biological implications and considerations.